1978
DOI: 10.1073/pnas.75.6.2584
|View full text |Cite
|
Sign up to set email alerts
|

Proposed temperature-dependent conformational transition in D-amino acid oxidase: a differential scanning microcalorimetric study.

Abstract: A number of authors have reported observations on D-amino acid oxidase [D-amino acid: 02 oxidoreductase (deaminating), EC 1.4.3.3] that they have interpreted in terms of a temperature-dependent conformational transition having a van't Hoff enthalpy amounting to more than 1 cal per g of protein (1 cal = 4.184J). No indication of this transition is obtained by using a differential scanning calorimeter having a sensitivity considerably in excess of that required to detect such a transition. The implications of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
11
0

Year Published

1980
1980
2003
2003

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 11 publications
2
11
0
Order By: Relevance
“…How can a substantial enthalpy change be detected by this spectroscopic analysis and not be calorimetry? Similar behavior has been observed for the protein d-amino-oxidase by Sturtevant and Mateo (1978) where the authors verified a reported fluorometric AH for the protein transition (Massey et al, 1965) but could not detect an enthalpy change calorimetrically. The discrepancies between the spectroscopic and calorimetric enthalpies can only mean that the microscopic AH as seen by changes in fluorophore environment does not reflect the true enthalpy change but rather relates to cooperative unit of the transition (Edsall and Gutfreund, 1983).…”
Section: Discussionsupporting
confidence: 79%
“…How can a substantial enthalpy change be detected by this spectroscopic analysis and not be calorimetry? Similar behavior has been observed for the protein d-amino-oxidase by Sturtevant and Mateo (1978) where the authors verified a reported fluorometric AH for the protein transition (Massey et al, 1965) but could not detect an enthalpy change calorimetrically. The discrepancies between the spectroscopic and calorimetric enthalpies can only mean that the microscopic AH as seen by changes in fluorophore environment does not reflect the true enthalpy change but rather relates to cooperative unit of the transition (Edsall and Gutfreund, 1983).…”
Section: Discussionsupporting
confidence: 79%
“…The binding interaction between apoproteins and flavin prosthetic groups has been studied extensively. The strong and specific binding of FMN or FAD to apoflavoproteins is driven by the enthalpic contribution to the free energy change of binding [40–42]. The thermodynamics of flavin binding to flavodoxin have been studied in detail [42–46].…”
Section: Thermodynamics Of Flavin Bindingmentioning
confidence: 99%
“…Their calorimetric studies, however, failed to show any concomitant change in heat capacity or enthalpy ofthe protein under identical conditions. This unequivocally rules out any thermodynamic transition and suggests that the fluorescence intensity reflects something other than the average conformational state of the protein (2).…”
mentioning
confidence: 99%
“…Given a fluorescence change, and assuming it to be a result of an equilibrium change in conformation, one might obtain the equilibrium constant for the transition from: K=F0 F(T) 2 F(7) [2] in which FO and F,,. are the low-and high-temperature limits of the fluorescence, respectively.…”
mentioning
confidence: 99%
See 1 more Smart Citation